AB0754 HOW DO WE TREAT PSORIATIC ARTHRITIS? EVIDENCE FROM A 15-YEAR MONOCENTRIC bDMARDs EXPERIENCE. (2nd June 2020) - Chimenti, M. S.; Ferraioli, M.; D'antonio, A.; Conigliaro, P.; Ferrigno, S.; Vendola, A.; Triggianese, P.; Fonti, G. L.; Perricone, R.
Abstract : Background: Psoriatic arthritis (PsA) treatment paradigm has dramatically change during the last 15 years, improving patients clinical outcomes and quality of life. We have now the possibility of a wide option among bDMARDs with different targets: TNF-inhibitors (TNFi), anti-IL17A inhibitors and anti-p40IL12/23. However, the choice of the "best" treatment in PsA patients is still a challenge in our daily clinical practice, making treatment decision a tricking issue. Objectives: Aim of the study was to retrospectively evaluate the distribution of clinical PsA subtypes and comorbidities among bDMARDs treated patients in the last 15 years in a monocentric cohort of the Rheumatology Unit, University of Rome Tor Vergata. Methods: Patients affected by PsA diagnosed by the CASPAR criteria and treated with a bDMARDs, in the last 15 years were enrolled. Clinical assessment included the presence of: oligo and/or polyarthritis and axial involvement (yes/no), enthesitis (yes/no), dactylitis (yes/no), PsO and onychopathy (yes/no). Comorbidities, as cardiovascular, metabolic syndrome and kidney diseases, were registered. The overall timeframe was halved in: 1st period (2004-2011) and 2nd period (2012-2019). Chi-square test was used to analyze the distribution of clinical PsA subtypes and comorbidities. Results: Data from 314 consecutive PsA patients treated with bDMARDs were obtained (Table 1). A total of 259 (82, 48%) patients were treated with TNFi, while 55 (17, 52%) with non-TNFi (i.e. Secukinumab, Ustekinumab or Apremilast). In the 1st period, 143 (86, 14%) patients were treated with TNFi and 23 (13, 85%) with non-TNFi; in the 2nd period, 116 (78, 4%) patients were treated with TNFi and 32 (21, 2%) with non-TNFi. PsA patients with polyarticular involvement were on TNFi in a higher prevalence in the first period than in the second (p<0.001). On the contrary, oligo-articular PsA and axial PsA were on TNFi in a higher prevalence in the 2nd period than in the 1st (p<0.001), as well as non-TNFi drugs were more frequently used in the 2nd period than in the 1st (p=0.03). PsA patients with PsO and/or onychopathy were in a higher prevalence on non-TNFi than on TNFi in the 1st period (p<0.001). PsA with enthesitis and/or dactylitis were in a higher prevalence on TNFi than on non-TNFi in the 1st period (p<0.001); this difference disappeared in the 2nd period, when both TNFi and non-TNFi were equally used (p=ns). PsA patients with metabolic syndrome and/or cardio-vascular and/or renal diseases were more prevalent on TNFi in the 1st period than in the 2nd while in the 2nd these patients were more frequently on non-TNFi (p<0.05). Conclusion: Here, we demonstrated that clinicians treatment choice in patients with moderate-severe PsA may be influenced by the clinical subtype and/or the occurrence of comorbidities. In particular, during the last years, the use of non-TNFi can be chosen more adequately as a therapeutical challenge in patients with different clinical manifestations and with comorbidities, improving PsA treatment paradigm. Disclosure of Interests: None declared